Optical Coherence Tomography in Cardiac Allograft Vasculopathy: State-of-the-Art Review. (20th August 2021) - Acharya, Deepak; Loyaga-Rendon, Renzo Y.; Chatterjee, Arka; Rajapreyar, Indranee; Lee, Kwan
Abstract : Cardiac allograft vasculopathy (CAV) is a challenging complication of heart transplantation. CAV pathophysiology is incompletely understood, standard screening modalities such as angiography have significant limitations, and currently available therapies have only modest efficacy in preventing progression. Optical coherence tomography is a light-based technique that provides microscopic level catheter-based intravascular imaging and has dramatically expanded our understanding of CAV, demonstrating it to be a complex, heterogeneous, and dynamic process. This review covers characteristics and uses of optical coherence tomography, including vessel characterization, serial use to assess progression of disease, guiding percutaneous intervention, and monitoring response to CAV therapies. We also discuss the potential of optical coherence tomography in providing individualized assessment and enable customized CAV therapies, which may lead to improvements in long-term transplant outcomes.